Simulation of munitions effects on ecosystem contamination in an Army range impact area - Houston, Stephen T., author; Shaw, R. B., advisor; Grigg, Neil, committee member; Redente, E. F., committee member; Laituri, Melinda J., committee member (Colorado State University. Libraries, 2002)
As a military service, the Army faces unique challenges in maintaining its warfighting readiness while practicing sound environmental stewardship of its training lands. The environmental implications of using firing ranges and impact areas are becoming more important. These include health and safety risks due to unexploded ordnance. Chemical contaminants such as Trinitrotoluene (TNT), Royal Demolition Explosive (RDX), and High Melting Explosive (HMX) are subject to environmental fate and transport processes congruent with the ecological setting into which they are released. An understanding and application of environmental and ecological science provides a vehicle for adequately addressing the impact area contamination problem. This dissertation demonstrates a methodology that integrates these disciplines into a problem solving approach that provides a foundation for effective resource management and future research. An ecological framework for assessment of environmental risk is used to evaluate the relative resilience of eleven major Army impact areas to explosive residue contamination. It identifies ecosystem properties that directly influence the rates of environmental fate and transport processes in the natural system. First approximations of munitions disturbance and contaminant loading are made and field data collected and analyzed from Fort Greely, Alaska. This yields a set of soil properties such as soil organic matter content that are related to an impact area's ability to attenuate contaminant fate and transport. Organic matter content of the soils proved to be a good predictor of cation exchange capacity and it also is a good descriptor of crater disturbance. SOM dynamics provides an integrative link between environmental process and ecological setting resolving the complex problem of impact area contamination into one that is more understandable and manageable. CENTURY SOM dynamics simulation adequately predicted levels of primary production and soil carbon for the modeled ecotypes of Fort Greely, Alaska. Simulated SOM rates-of-change resulting from munitions use provided insight into ecological and environmental processes affecting munitions contamination, and the ability to quantify contaminant attenuation. Finally, a geographic information system enables an integrated analysis that produces an environmentally and ecologically based measure of the system's ability to attenuate contamination for use in decision making.
Keywords: ecology; environmental science